A Hubungan Pengetahuan dan Kepatuhan Diet dengan Kadar Gula Darah pada pasien Diabetes Melitus Di Poli Penyakit Dalam RSUD Idaman Banjarbaru Tahun 2018 - Tri Ardianti Khasanah; Zul Fina Fitri (HB PRESS, 2019)
Diabetes mellitus is a chronic metabolic disorder due to the pancreas not producing enough insulin or the body cannot use insulin that is produced effectively. Indonesia has 10.3 million sufferers and standon 7th position in the world after China, India, United States of America, Brazil, Russia, Mexico, on 2017 at the province of South Kalimantan’s on 2nd position that were 10.875, at Banjarbaru in 2017 is held on 2nd ranked which had 2.968 cases, at Idaman Banjarbaru Hospital on the Internal Medicine Polyclinic there were 394 patients from January till April and estimated that will be 100 diabetes mellitus patients. This research is aimed to knowing the correlation of knowledge and compliance of diet with blood sugar levels of patients with diabetes mellitus at the Internal Medicine Polyclinic in Banjarbaru Hospital 2018. This type of research is a description of correlation research using cross sectional design. This research was carried out to 55 respondents. The results that tested using Chi-Square with a value of α=0.1 proved to have no correlation of knowledge with blood sugar levels (p=0.234) and proved to have a correlation of adherence to diet with blood sugar levels (p=0.00). From this study it can be concluded that knowledge proved to have not correlation with blood sugar levels and dietary compliance was shown to have a correlation with blood sugar levels in diabetes mellitus patients at Internal Medicine Polyclinic Idaman Banjarbaru Hospital 2018.